Introduction of Web based Continuous Professional Development to Sri Lanka - Kulatunga, G.G.; Marasingha, R.B.; Karunathilake, I.M.; Dissanayake, V.H.W. (Sri Lanka Journal of Bio-Medical Informatics, 2013)
Continuous Professional Development (CPD) can be described as a continuous process which begins on the day a person start practicing as a doctor. Continuous Medical Education (CME) concentrates on improving individual professional knowledge by education and training in areas determined by experts. But in CPD, professionals play an active role in defining the knowledge which they see as relevant to their own professional needs and learning takes place not only at individual level but also at organisational level. CPD is becoming a popular mode of learning worldwide by which doctors keep their practice up to-date. CPD is seen as essential for effective practice and for professional development. Even though the standard format of CPD for many years has been formal, there is no specific method in operation. Over the last decade there has been increasing interest in the use of computers to facilitate collaborative learning between healthcare professionals for CPD. Web-based learning is an attractive methodology for medical education and offers some advantages over traditional methods. There is improved clinical practice and improved clinical decision making as a result of web based learning. Professionals are satisfied with the ﬂexibility and the convenience offered in Web-based mode of CPD delivery as it saves time and money. Web based CPD programmes will fulfil the educational requirements of health professionals in the peripheral parts of Sri Lanka who have difficulty in attending formal education sessions due to their geographical isolation. Meeting the educational needs of professionals already in practice remains a challenge and web based online CPD can play a major role in proving the high demand.
Keywords: CPD; CME; e-learning; Information Communication Technology